Fracture resistance of ceramics: edge fracture method - Gogotsi, G.A.; Galenko, V.I.; Ozerskii, B.I.; Khristevich, T.A. (Проблемы прочности, 2005)
Fracture resistance o f macrohomogeneous line ar elastic yttria, scandia, alumina, zirconia, and silicon nitride ceramics was studied upon flaking of the edges of rectangular specimens with the Rockwell indenter. The correlation between the obtained estimates and fracture toughness test results gained by the single-edge V-notched beam method was demonstrated. Loads giving rise to the flaking of a part of the edge and distances from this edge to the chip scar on the specimen surface were measured. The ratio of those values was considered as a flaking toughness characteristic. The data obtained were statististically reliable (based on more than a hundred determinations). This procedure termed the edge fracture method can be used along with other known fracture toughness test methods for ceramics, its application is especially advantageous when ceramic item sizes are comparable with those of the standard specimens or when expensive materials (e.g., nanoceramics) are tested.